A systemic review and meta-analysis comparing the ability of diagnostic of the third heart sound and left ventricular ejection fraction in heart failure - Dao, Lin; Huang, Min; Lin, Xinghong; Li, Liuyin; Feng, Xixi; Wei, Changyou; Guo, Mingjin; Yang, Yifan; Xu, Fan; Weng, Xiechuan (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aimed to compare the sensitivity and specificity of diagnosis between the third heart sound (S3) and left ventricular ejection fraction (LVEF) in heart failure (HF). Methods: Relevant studies were searched in PubMed, SinoMed, China National Knowledge Infrastructure, and the Cochrane Trial Register until February 20, 2022. The sensitivity, specificity, likelihood ratio (LR), and diagnostic odds ratio (DOR) were pooled. The symmetric receiver operator characteristic curve (SROC) and Fagan’s nomogram were drawn. The source of heterogeneity was explored by meta-regression and subgroup analysis. Results: A total of 23 studies, involving 6307 participants, were included. The combined sensitivity of S3 was 0.25 [95% confidence interval (CI) (0.17–0.36), specificity was 0.94 [95% CI (0.85–0.98)], area under the SROC curve was 0.54, and the DOR was 5.76; while the sensitivity of LVEF was 0.83 [95% CI (0.65–0.92)], specificity was 0.83 [95% CI (0.75–0.88)], area under the SROC curve was 0.88, and the DOR was 22.34. No publication bias was detected in Deeks’ funnel plot. The prospective design, partial verification bias, and blind contributed to the heterogeneity in specificity, while no sources contributed to the heterogeneity in sensitivity. In Fagan’s nomogram, the post-test probability was 53% when the pre-test probability was set as 20%, while in LVEF, the post-test probability was 54% when the pre-test probability was set as 20% Conclusion: The use of S3 alone presented lower sensitivity and specificity in diagnosing HF compared with LVEF, whereas it was useful in early pathological assessment.